In vitro study of the proliferation and growth of human fetal osteoblasts on Mg and Si co‐substituted tricalcium phosphate ceramics. Issue 8 (17th May 2017) - Parra, Juan; García Páez, Ismael H.; De Aza, Antonio H.; Baudin, Carmen; Rocío Martín, M.; Pena, Pilar
Abstract: The objective of this work was to study the feasibility of the solid state sintering, a conventional ceramic processing method, to obtain Mg and Si co‐substituted tricalcium phosphate bioceramics and composites containing diopside. A series of new Ca3 (PO4 )2 based ceramics has been prepared from attrition milled mixtures of synthetic Ca3 (PO4 )2 and CaMg(SiO3 )2 powders, isostatically pressed and sintered at 1250–1300°C. Materials containing 0, 1, and 5 wt % of CaMg(SiO3 )2 were constituted by β + α ‐ Ca3 (PO4 )2 solid solutions while the material containing 60 wt % of CaMg(SiO3 )2 was a constituted by β‐ Ca3 (PO4 )2 and CaMg(SiO3 )2 . The biological responses of the developed ceramics were studied in vitro using human fetal osteoblast cultures. Culture times ranged from 1 to 21 days. The new family of materials promotes the adhesion and proliferation of human osteoblasts cultured onto their surface forming a monolayer and showing a normal morphology. The results of the MTT and Alamar Blue assays showed that the soluble components extracted from the Mg/Si‐ co‐substituted Ca3 (PO4 )2 and the Ca3 (PO4 )2 ‐CaMg(SiO3 )2 composite were noncytotoxic. The specimens with diopside exhibited a better in vitro behavior which is attributed to the release of Si and Mg ions to the culture medium, enhancing the activity of cells. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2266–2275, 2017.